Experimental investigation of flow visualization of vortex shedding on a flow over square block. (2021) - Sivasubramanian, M.; Jaganathan, K.D.; Ramkumar, P.
Abstract: Flow visualization is one of the important constituent of technical research work for the long time. Learning on separate and step flow is the topic of attention for decades in extensive engineering uses like chilling of devices like electronics, thermal exchangers, turbine and many equipment operates under thermal situations. Current exploration is to depict the impact of the flat plate with block in restricted atmosphere. Recirculation eddy size, Recirculation centre and flow visualization for various Reynolds number ranging from 800 to 1500 and spacing between center to center distance (Lx /Ly  = 2), are the constraints described when water is used as the operational fluid. Crystal Violet paint is used for flow visualization and tint addition method is take on for the visualizing the field of flow. The outcome of the present investigation shows that, increase in the Reynolds number from 800 to 1500 tends to increase in the reattachment length therby the Centre of vortex, Size of vortex and Reattachment length also increases.